(3eaJGM GdLGeY HeaGJjM GdTQGFYs - (3GdHgHGfj, GdCUHgGfj, eMeO Ydj Hf eMeO HGbQ, J (B1216 (3g`s
(3ChdgG (B:s
(3cJGH GdRcGI (B.. (3bhdg hGdfUhU gh ceG bGd hde jYJQV dPcQ ELeGY GdeSdejf hGdaQGOI eY Cf hLhHgG aj VQhQjGJ GOjf bGd aj GdJPcQI CLeY GdeSdehf cGbI Ydi hLhHgG aj LejY GdGYUGQ (B...s
(3BNQgG (B:s
... (3hdO GdRfG dG fSH dg TQYG ef WQb GdRfG ceG gh XGgQ heY Pdc HYV GdKeQGJ GdTQYjI jJMbb ajg eKd YOe JLhjR fcGM GdCHfI hGdCe GHfgG hEf cGf ef GdRfG ceG Mbb aj eMdg (B... (3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\535s
(3EjVGM Gdecfhf (B2 \523s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis